Formulation And Statistical Tools Used To Optimization Of Media Components For Enhancement Of Antibiotic Production By Streptomyces Geysiriensis Lk8 - Leena Patel; Kamleshkumar Shah; Rajesh Patel; Vipul bhinsara; Aquino Alex Macwan (The Bioscan, 2024)
Antibiotic resistance in bacteria presents a major challenge to public health, necessitating the search for new antibiotics. Streptomyces geysiriensis lk8, isolated from the saline desert of the Rann of Kutch, India, shows potential for antibiotic production. This study aimed to optimize the cultural and nutritional conditions for antibiotic production using Response Surface Methodology (RSM) and Design Expert software.